2013
DOI: 10.1080/14729679.2012.702532
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor education gives fewer demands for action regulation and an increased variability of affordances

Abstract: In children's lives there are a lot of instigators for actions in every milieu and situation. When children grow older, the cortical activity starts to regulate the action instigation from the limbic system. The school system makes demands of action regulation for children. In outdoor education the many instigators for actions are not under the same demands for regulation as inside the classroom. In this study we have interviewed nine children about their experience with outdoor education. The interviews shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 34 publications
2
28
0
2
Order By: Relevance
“…Table 2 shows specific information concerning the interventions and data collections. Four studies were conducted in Denmark [4,6,7,27], three in the USA [28,29,30], and one each in Germany [23], New Zealand [31], Sweden [5], the UK [32], and Norway [33]. One study included data from the UK, India and Kenya [34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 shows specific information concerning the interventions and data collections. Four studies were conducted in Denmark [4,6,7,27], three in the USA [28,29,30], and one each in Germany [23], New Zealand [31], Sweden [5], the UK [32], and Norway [33]. One study included data from the UK, India and Kenya [34].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies collected and analysed data on a solely student level [4,23,27,29,34,35], five studies also included data from teachers, staff and parents [6,30,31,32,33] and one study [5] only included data from parents. Eight studies used interviews [6,27,29,30,31,32,33,34], six studies used questionnaires [5,7,28,30,31], three studies used learning assessments [29,30,31], two studies used observations [32,34] and, in each case, one study used a postal survey [23], written documents [29], drawings and concept maps [34], and accelerometry [4]. The quantity of compulsory educational activities in a natural or cultural environment outside the classroom varied from one school day bi-weekly to a duration of eight weeks [27], and a six-month full week programme [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The boys seemed to be more active, explorative and, in a much higher degree, they did activities which they were not able to do at the ordinary school environment. (Fiskum & Jacobsen, 2012), but whether they really differ in their actions during those days, remains to explore.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown outdoor education as a useful intervention to reduce undesirable behavior, such as different degrees of agitations, as well as to vitalize the children, provides a positive experience and increases the amount of desirable behavior like for example, more focus on task and more holistic presence (Dyment, 2005;Dyment & Bell, 2008;Fiskum & Jacobsen, 2012b, Contingent events, frustration or satiation are the main factors which might bring us to reversals from one state to another (Apter, 2001). These reversals are not anything we are making by free will; they are being guided by the situation (contingency, frustration and satiation) and our personality (dominance and liability to easily change state) (Apter, 2001).…”
Section: Introductionmentioning
confidence: 99%